Hubungan Menu Anxiety, Pemilihan Makanan, dan Kebiasaan Makan pada Status Gizi Generasi Z di Cinere, Depok: The Relationship between Menu Anxiety, Food Preference, Eating Habits, and the Nutritional Status of Generation Z in Cinere, Depok - Anwar, Khoirul; Putri, Fathiarica Sharifa; Maskar, Dadi Hidayat (Amerta Nutrition, 2024)
Background: Generation Z is driving modern shopping trends influenced by technology. One of the emerging phenomena is Menu anxiety, which is described as the feeling of anxiety in choosing food. This condition can potentially lead to suboptimal nutritional intake, affecting the nutritional status. Objectives: The present study aimed to analyze the relationship between anxiety menu, food selection, eating habits, and the nutritional status of Generation Z in Cinere area, Depok. Methods: It used a cross-sectional research design with 90 Generation Z subjects aged 16-18 years at Dian Didaktika Islamic Private High School (SMAS), Cinere, Depok. The data collected included subject characteristics, Eating habits, and eating patterns based on the Food Frequency Questionnaire (FFQ). Weight and height were measured directly. A bivariate test was used with Spearman Rank. Results: As many as 65.5% of subjects experienced menu anxiety, with 86.2% choosing a menu based on taste. The main reasons for difficulty in choosing a menu were fear of regret (41.4%) and menu choices (26.4%). Subjects consumed fruits (46.0%) and vegetables (40.2%) about 2-4 days/week, and had good nutritional status. There was a relationship between the frequency of eating out and the nutritional status of the subject based on the Body Mass Index by age (BMI/A) (p-value=0.019, r=0.252), but there was no significant relationship between the habit of eating fruit, vegetables, sweet snacks and sweet drinks and the nutritional status (p-value>0.05). Conclusions: Eating out habits are related to nutritional status. Menu anxiety, consideration in food selection, and consumption of fruits, vegetables, sweet snacks, and sweet drinks do not have any relationship with nutritional status.